The Operational Consequences of Private Equity Buyouts: Evidence from the Restaurant Industry - Bernstein, Shai; Sheen, Albert (Review of Financial Studies, 2016)
How do private equity firms affect their portfolio companies? We document operational changes in restaurant chain buyouts using comprehensive health inspection records. Store-level operational practices improve after private equity buyout, as restaurants become cleaner, safer, and better maintained. Supporting a causal interpretation, this effect is stronger in chain-owned stores than in franchised locations—“twin” restaurants over which private equity owners have limited control. These changes are particularly apparent when private equity partners have prior industry experience. The results suggest that by bringing in industry expertise, private equity firms improve firm operations. Received October 27, 2014; accepted March 1, 2016 by Editor Francesca Cornelli.